Analisis Kegagalan Pasangan Calon Husain Alting Sjah dan Asrul Rasyid pada Pilgub Malut 2024 - Septiadi, Ferdi Rama; Mahmudi, Idlan Dziqri; Rachdical, Muamar Safrit; Putranto, Algooth (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the failure of the candidate pair Husain Alting Sjah and Asrul Rasyid in the 2024 Maluku Utara Gubernatorial Election (Pilgub Malut). This election is crucial for regional political dynamics as it involves strategic figures and influences future policy directions. The research background focuses on understanding the main factors that contributed to the defeat, which may include social, political, and economic aspects. The study employed a literature review method, utilizing data from official documents, media reports, and relevant research findings. The analysis reveals that the candidates faced significant challenges, including insufficient internal consolidation within the campaign team, political communication strategies that failed to reach all societal layers effectively, and weaker political networks compared to their competitors. External factors, such as the dominance of rivals with broader support bases and more effective mobilization capabilities, also contributed to the loss. The study concludes that Husain Alting Sjah and Asrul Rasyid were unable to fully capitalize on their social and political assets to compete effectively. This research provides theoretical contributions to the study of political strategies in local elections, particularly in the Maluku Utara region, and offers practical insights for candidates in preparing political strategies in the future.